A Retrospective Review of Children followed up with the Diagnosis of Acute Pancreatitis - Deveci, U.; Unsal, S. K.; Dogan, Y. (Wolters Kluwer Medknow Publications, 2023)
Background: Acute pancreatitis (AP) is an inflammatory disease of the pancreas, the frequency of which increases in childhood. Aim: To investigate the demographic, etiological, clinical, laboratory, and radiological characteristics of children followed up with the diagnosis of AP. The study also included genetic studies of recurrent cases. Materials and Methods: This retrospective cohort study included pediatric patients <18 years of age with AP who were followed up with recurrent pancreatitis in the Pediatrics Department of a University Hospital between January 2010 and April 2021. Patients who met at least 2 of the 3 criteria defined by the International Pediatric Pancreatitis Study Group (INSPPIRE) were accepted as AP. Demographic, etiological, and clinical data of the patients, developing complications, pathological evaluation of the samples, and genetic analysis results were obtained from the patient files. The obtained data were statistically analyzed using the SPSS version 26.0 program. Descriptive statistics of the data were expressed as mean +/- standard deviation, median, minimum and maximum values, number (n), and percentage (%). Kolmogorov-Smirnov test, Mann Whitney U test, Chi-square test and Fischer test were used. Results: Fifty-four (50%) female and 54 (50%) male patients with a mean age of 9.96 +/- 4.8 years who met the study criteria were included in the study. In the follow-up, it was reported that acute recurrent pancreatitis developed in 23 (21%) patients and chronic pancreatitis developed in 8 (7%) patients. The most common complaints were abdominal pain (94.4%), and vomiting (60.2%), followed by malnutrition (36.1%), nausea (17.6%), diarrhea (13%), and fever (13%). Etiology could not be determined in 19.4% of the patients. It was noted that the genetic predisposition of the patients played a role in the development of recurrent and chronic pancreatitis. Amylase, lipase, and CRP values, which are among the laboratory parameters showing the severity and prognosis of AP, were found to be significant. Conclusions: Sociocultural and demographic data of the patients should also be taken into account. Gene sequences that cause to genetic predisposition should be determined in recurrent and chronic pancreatitis cases. Acute pancreatitis should be considered in the differential diagnosis of patients with frequent abdominal pain and vomiting.
Keywords: Acute pancreatitis; child; etiology; serum C-reactive protein